Strategies in Learning and Techniques in Teaching English Speaking - Noviyenty, Leffi (Sekolah Tinggi Agama Islam Negeri (STAIN) Curup, 2018)
Learning how to speak English fluently and accurately is always a grand task for foreign students. Strategies in learning to speak as one of important factors of speaking skill should be considered not only by foreign students but also the teachers. Studentsâ strategies in learning to speak English should be in balance with teachersâ techniques in teaching students to speak English. Both affect the improvement of studentsâ ability in speaking English. This research is descriptive which tries to describe and elaborate the students of SMAN 1 Curupâs strategies in learning to speak English and their English techniques in teaching them to speak. There were 47 third year students selected as the sample from 8 classes and 7 English teachers. The instruments used in this study were questionnaire which were given both to the students and teachers with different items and also interview guidance. The findings showed that the strategies used by SMAN 1 Curupâs students in learning to speak English were classified into metacognitive strategies, cognitive strategies, social strategies, and affective strategies. The English teacher techniques in teaching student were roleplay, group presentation, group discussion, speech competition, dialogues, direct correction, speaking in group, debate competition, games, and listening song. Keyword : Studentsâ Strategies, Speaking, Teachersâ Techniques